Javanese and Sundanese Swear Words in the Film Yowis Ben 2: A Sociopragmatic Study - Febriyatko, Angga; Ambarwati, Ari; Osman, Zulkifli bin; Rahmawati, Cut Dian (Universitas Muhammadiyah Malang, 2023)
Swearing is used in every human language activity. Swearing can be found in films as a form of literary work that provides entertainment and describes the phenomenon of social reality. The Yowis Ben 2 film is a youth comedy genre film that contains swear words using local languages, Javanese and Sundanese. This research focuses on a sociopragmatic study of Javanese and Sundanese swearing in the film Yowis Ben 2 to look at the references, functions, and implicatures of swearing speech acts in both languages. This study uses a qualitative descriptive research method. The primary data is in the form of swearing in Javanese and Sundanese in the form of words, phrases, sentences, and scenes for each character in the film, and the secondary data is in the form of previous studies related to swearing in Javanese and Sundanese. Data collection techniques are carried out by documenting, listening, recording, and analyzing content. Data analysis techniques are carried out by reducing, presenting, and drawing conclusions and by using pragmatic equivalent studies in order to reveal swearing implicatures in two languages. The results of the research show that not all swearing in Javanese and Sundanese languages found in the film